Delving into somatic variation in sporadic melanoma - Walia, Vijay (2012)
Melanoma, the most aggressive form of skin cancer, has increased in incidence more rapidly than any other cancer. The completion of the human genome project and advancements in genomics technologies has allowed us to investigate genetic alterations of melanoma at a scale and depth that is unprecedented. Here, we survey the history of the different approaches taken to understand the genomics of melanoma – from early candidate genes, to gene families, to genome-wide studies. The new era of whole-exome and wholegenome sequencing has paved the way for an in-depth understanding of melanoma biology, identification of new therapeutic targets, and development of novel personalized therapies for melanoma.